Pathomorphological features of clinical forms of ulcerative colitis in children - M.F. Denysova; T.D. Zadorozhna; N.Yu. Bukulova; T.М. Archakova (Zaslavsky O.Yu., 2021)
Background. Ulcerative colitis is a chronic inflammatory disease of unknown origin, characterized by a clinically recurrent course with periods of bloody diarrhea and pathomorphological-diffuse inflammatory process in the colon. The problem of ulcerative colitis requires further study of the clinical features of the disease, taking into account the localization, degree of activity of the inflammatory process, changes in the structure of the mucous membrane that will help increase the efficiency of ulcerative colitis diagnosis in childhood. Materials and methods. On the basis of clinical and statistical analysis of 116 case histories of children aged 4-18 years with ulcerative colitis, the features of its clinical forms - total, segmental and distal - were studied during the period of exacerbation of the disease. Four hundred and forty-five biopsy specimens obtained during colonoscopy were histologically examined. After biopsy sampling, specimens were fixed in 10% formalin and were processed according to the generally accepted histological method with section staining using hematoxylin-eosin and according to Van Gieson. Results. Changes in the architectonics of the large intestine mucosa, which reduce the resistance of the mucous barrier, as well as impaired blood supply - a factor in the development of hemic hypoxia - are significant for the mechanisms of ulcerative colitis exacerbation.